IMPLEMENTATION OF THE TRANSFER OF LAND RIGHTS HAS NOT BEEN CERTIFIED USING A DEED OF SALE AND PURCHASE TO THE LAMONGAN COMMUNITY IN EAST JAVA - Dimas Surya Pratama; Nynda Fatmawati Octarina (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
Transfer of rights to land is the transfer of rights to land plots from one party to another in the process of buying and selling a land object. In its implementation, strong evidence is needed in the transfer of land rights so that there is no dispute in the future that harms one of the parties in the sale and purchase of land objects. In its implementation, there are often problems related to the transfer of rights to land that has not been certified. Government Regulation Number 24 of 1997 concerning Land Registration states that for the purposes of transferring rights to the Land Office, the sale and purchase of land rights must be proven by a PPAT deed. Proof of PPAT deeds is important in the transfer of land rights to strong evidence and is recognized by the state as an official authorized to make deeds in accordance with interests. The deed made by PPAT is a requirement to register the land in order to get a certificate on the land.